Analisis Faktor-faktor yang Mempengaruhi Customer Trust dan Repurchase Intention Pada Aplikasi Quick Commerce - Panca Ardhio Saputra; Usep Suhud; Diena Noviarini (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study analyzes the influence of e-service quality, product quality, and brand image on customer trust and repurchase intention among users of the ASTRO quick commerce application. The rapid development of quick commerce has increased competition, making customer trust a key factor in encouraging repeat purchases. This research uses a quantitative approach with a survey method conducted through online questionnaires distributed via Google Forms. The sample consists of 240 respondents aged at least 17 years, domiciled in DKI Jakarta, and having made at least one purchase using the ASTRO application. The data collected are primary data and were analyzed using SPSS version 29 and AMOS version 23 with Structural Equation Modeling. The results show that e-service quality, product quality, and brand image have a positive and significant effect on customer trust. These variables also have a positive and significant influence on repurchase intention. Additionally, customer trust is proven to have a positive and significant effect on repurchase intention, highlighting its important role in driving repeat purchase behavior in quick commerce services. This study provides managerial implications for improving service quality, product quality, and brand image to strengthen customer trust and repurchase intention. Keywords: Brand Image; Customer Trust; E-service Quality; Product Quality; Repurchase Intention Abstrak Penelitian ini menganalisis pengaruh e-service quality, product quality, dan brand image terhadap customer trust dan repurchase intention pada pengguna aplikasi quick commerce ASTRO. Perkembangan layanan quick commerce yang semakin pesat mendorong persaingan yang ketat antar platform, sehingga customer trust menjadi faktor penting dalam mendorong repurchase intention. Tujuan penelitian ini adalah untuk mengetahui sejauh mana e-service quality, product quality, dan brand image memengaruhi customer trust serta repurchase intention. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei melalui penyebaran kuesioner daring menggunakan Google Form. Sampel penelitian terdiri atas 240 responden yang berusia minimal 17 tahun, berdomisili di DKI Jakarta, dan pernah melakukan setidaknya satu kali pembelian melalui aplikasi ASTRO. Data yang digunakan merupakan data primer yang dianalisis menggunakan SPSS versi 29 dan AMOS versi 23 dengan metode Structural Equation Modeling. Hasil penelitian menunjukkan bahwa e-service quality, product quality, dan brand image berpengaruh positif dan signifikan terhadap customer trust. Selain itu, ketiga variabel tersebut juga berpengaruh positif dan signifikan terhadap repurchase intention. Penelitian ini memberikan implikasi manajerial bagi perusahaan dalam meningkatkan e-service quality, product quality, dan brand image guna memperkuat customer trust serta repurchase intention. Kata kunci: Brand Image; Customer Trust; E-service Quality; Product Quality; Repurchase Intention